2020
DOI: 10.1186/s13063-019-3944-9
|View full text |Cite
|
Sign up to set email alerts
|

Global mapping of randomised trials related articles published in high-impact-factor medical journals: a cross-sectional analysis

Abstract: Background: Randomised controlled trials (RCTs) provide the most reliable information to inform clinical practice and patient care. We aimed to map global clinical research publication activity through RCT-related articles in highimpact-factor medical journals over the past five decades. Methods: We conducted a cross-sectional analysis of articles published in the highest ranked medical journals with an impact factor > 10 (according to Journal Citation Reports published in 2017). We searched PubMed/MEDLINE (fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 109 publications
1
20
0
Order By: Relevance
“…It was surprising that we only identified 29 articles (14 trials) considering the large and increasing quantity of RCTs published every year [ 52 ]. This finding suggests greater efforts are needed to ensure researchers understand the importance of undertaking process evaluations in the acute hospital setting especially the barriers and facilitators to intervention uptake.…”
Section: Discussionmentioning
confidence: 99%
“…It was surprising that we only identified 29 articles (14 trials) considering the large and increasing quantity of RCTs published every year [ 52 ]. This finding suggests greater efforts are needed to ensure researchers understand the importance of undertaking process evaluations in the acute hospital setting especially the barriers and facilitators to intervention uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the impactful literature globally (e.g., research articles and books) has been written in a dominant language (e.g., English, Spanish, Chinese). 9 Authors commonly prefer to publish in these languages, most commonly English, to increase the visibility and impact of their publication. 10 , 11 However, these selective preferences may act as a barrier to research dissemination for researchers who are not fluent in English.…”
Section: Scientific Literaturementioning
confidence: 99%
“…Researchers who speak languages other than English and that have a greater impact, such as Spanish, French, or German, are still overrepresented in high-income countries. 9 The result is an omission of most researchers, mainly from LMICs where these languages are often not an additional language or the researchers are not fluent in English.…”
Section: Scientific Literaturementioning
confidence: 99%
“…The number of randomised trial related articles published in prominent medical journals has increased considerably in recent decades (Catalá-López et al, 2020 ). Randomised trials, when appropriately conducted and reported, can provide the most reliable information on the efficacy of interventions for informing healthcare decision-making.…”
Section: Introductionmentioning
confidence: 99%